The Intersection of Human Development and Poverty: An Analysis of HDI and I-HDI in Yogyakarta based on Maqāşid Syarī’ah - Abdullah Haidar; Dedy Rachmad (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
Despite its high Human Development Index (HDI), Yogyakarta paradoxically suffers from one of the highest poverty rates on the island of Java. This situation underscores the limitations of conventional human development metrics, particularly in regions with a predominantly Muslim population. To address this issue, this study introduces the Islamic Human Development Index (I-HDI) as an alternative framework that more effectively captures the relationship between human development and poverty in a Muslim-majority context. Utilizing secondary data from five districts in Yogyakarta spanning the years 2012 to 2023, and employing panel data regression alongside Granger causality analysis, the findings indicate that HDI has a limited and indirect effect on poverty. In contrast, I-HDI demonstrates a stronger and more direct negative correlation with poverty levels. Furthermore, Granger causality analysis reveals that changes in I-HDI significantly influence poverty levels, and vice versa, suggesting a dynamic and bidirectional interaction between these two variables. These results imply that I-HDI offers a more accurate reflection of human development in Muslim-majority regions, capturing dimensions often overlooked by traditional indices. Ultimately, the findings highlight the intricate interaction between human development and poverty, providing valuable insights for policymakers to create more effective poverty alleviation strategies grounded in Islamic principles and local cultural values.